GG-NER’s role in androgen receptor signaling inhibitor response for advanced prostate cancer - Chuanfan Zhong; Jiaxing Wang; Hangyang Peng; Jianming Lu; Zining Long; Zhuoyuan Lin; Guo Chen; Chao Cai; Shilong Cheng; Zhongjie Chen; Le Zhang; Weibo Zhong; et al. (Cell Communication and Signaling)
Abstract Background Advanced prostate cancer (PCa) often initially responds to androgen receptor signaling inhibitors (ARSI) but frequently develops resistance, driven by tumor heterogeneity and therapeutic pressure. Addressing the clinical challenge of identifying non-responsive patients and discovering new therapeutic targets is urgently needed. Methods We utilized single-sample gene set enrichment analysis (ssGSEA) to elucidate the influence of the GG-NER pathway on ARSI response in PCa. We then constructed and validated a prognostic model based on this pathway using LASSO regression, Kaplan-Meier analysis, Cox regression, and ROC analysis. Additionally, we mapped tumor mutations to delineate the mutational landscapes across different risk groups and explored functional pathways through GO, KEGG, and GSEA analyses. The impact of the GG-NER pathway on enzalutamide sensitivity and DNA repair in PCa was further validated through CCK-8 assays, colony formation assays, in vivo experiments, and immunofluorescence. Results ssGSEA indicated a trend of GG-NER pathway upregulation in patients with poor ARSI response. The GG-NER characteristic gene score (NECGS) identified a high-risk group with diminished ARSI response, serving as an independent prognostic indicator with strong predictive power. This high-risk group exhibited elevated TP53 mutation frequencies and significant enrichment in key pathways such as ribosome and mitochondrial functions, as well as MYC and E2F signaling. Experimental validation confirmed that targeting the GG-NER pathway or its key gene, ACTL6A, significantly reduces enzalutamide resistance in resistant cell lines and increases γH2AX expression. Conclusion NECGS effectively predicts ARSI response in PCa, and our comprehensive analysis underscores the critical role of the GG-NER pathway in enzalutamide resistance, positioning ACTL6A as a potential therapeutic target for PCa.